Assessment of Knowledge of Final Year Undergraduate Dental Students about Lasers and their Use in Pediatric Dentistry - Priya Mendiratta; Pooja Srivastava; Gauri Kalra; Bhavna G Saraf; Neha Sheoran (Journal of South Asian Association of Pediatric Dentistry)
Aims and objectives: This study aims to assess the knowledge and awareness of undergraduate final year dental students regarding the applications of lasers in pediatric dentistry and the need for introducing theoretical and practical classes in their curriculum. Methodology: A cross-sectional survey was conducted among 106 fourth year dental students of an institute in Faridabad. A self-administered questionnaire consisting of 19 questions related to general knowledge and applications of lasers in pediatric dentistry and about its safety aspects was given to the students, and responses were analyzed to obtain the results. Results: About 99% of participants knew what laser is and 93.4% of the respondents knew about its applications in pediatric dentistry; however, in-depth knowledge of students regarding soft and hard tissue procedures and its use in cavity and crown preparation was below satisfactory. Awareness about safety and hazards was also inadequate. Conclusion: Considering many applications and possible advantages of increasing cooperation in pediatric patients, lasers should be incorporated both in theory and practical in the undergraduate curriculum of pediatric dentistry.